Comparison of the performance of laboratory tests in the diagnosis of feline infectious peritonitis. (May 2018) - Stranieri, Angelica; Giordano, Alessia; Paltrinieri, Saverio; Giudice, Chiara; Cannito, Valentina; Lauzi, Stefania
We compared the performance of clinicopathologic and molecular tests used in the antemortem diagnosis of feline infectious peritonitis (FIP). From 16 FIP and 14 non-FIP cats, we evaluated retrospectively the sensitivity, specificity, and likelihood ratios (LRs) of serum protein electrophoresis, α1 -acid glycoprotein (AGP) on peripheral blood, screening reverse-transcription nested PCR (RT-nPCR) on the 3'–untranslated region (3'-UTR), and spike (S) gene sequencing on peripheral blood, body cavity effusions, and tissue, as well as body cavity cytology and delta total nucleated cell count (ΔTNC). Any of these tests on blood, and especially the molecular tests, may support or confirm a clinical diagnosis of FIP. A negative result does not exclude the disease except for AGP. Cytology, 3'-UTR PCR, and ΔTNC may confirm a clinical diagnosis on effusions; cytology or 3'-UTR PCR may exclude FIP. Conversely, S gene sequencing is not recommended based on the LRs. On tissues, S gene sequencing is preferable when histology is highly consistent with FIP, and 3'-UTR PCR when FIP is unlikely. Combining one test with high LR+ with one with low LR− (e.g., molecular tests and AGP on blood, ΔTNC and cytology in effusions) may improve the diagnostic power of the most used laboratory tests.